Study of Flame Spray Coated Fe-Al Using N2 as a Gas Carrier. (March 2019) - Timuda, G E; Hermanto, B; Sudiro, T
Abstract: We studied the effect of using N2 as a gas carrier on the structural and mechanical properties of Fe-Al coating. Typically, using air as the gas carrier in flame spray coating method was prone to the formation of intrinsic Fe-oxide(s), thus reducing its further resistance against oxidation at elevated temperature. The use of N2 to replace air as the gas carrier was conducted in this research to minimize the possible Fe-oxide(s) formation. We found that there were still Fe-oxide (wuestite) formed even after the replacement, indicating the contribution of O2 gas used in the fuel mixture (Acetylene/O2 ) and/or oxygen from the environment on the oxidation. Further optimization was then conducted by tuning the Acetylene/O2 gas ratio under N2 gas carrier and cooling down the sprayed samples under N2 gas exposure. Samples free of Fe-oxide(s) species thus have been successfully obtained. The effect of spraying distance was also studied to improve the intermetallic formation. Higher hardness of the shorter distance samples gives early indication of the improvement of mechanical properties induced by the intermetallic formation.